Parvovirus H-1 infection of human glioma cells leads to complete viral replication and efficient cell killing - Herrero y Calle, Marta; Herold-Mende, Christel; Rommelaere, Jean; Schlehofer, Jörg R.; Geletneky, Karsten (International journal of cancer, 2004)
The extremely poor prognosis of malignant gliomas requires the investigation of other than standard therapies, i.e., the application of oncolytic viruses. In our study, we evaluated the effects of the oncosuppressive parvovirus H-1 on different established glioblastoma cell lines of rat and human origin and on short-term/low-passage cultures of human glioblastoma cells. We observed an efficient and dose-dependent killing of all glioma cell cultures at low multiplicities of infectious particles (MOI) per cell. Southern blot analysis of viral DNA amplification, RT-PCR analysis of viral RNA expression and Western blot analysis of the expression of viral structural (VP-1/VP-2) and nonstructural (NS-1) proteins demonstrated the biosynthesis of these viral macromolecular components in all of the cultures. Moreover, all the glioma cells were proficient for the production of infectious H-1 virus particles. The amount of virus production differed between a several fold increase of the input virus titer in most of the short-term/low-passage cultures up to 1,000-fold in one short-term glioma and in the rat cells. Glioma cells lines and, more importantly, short-term/low-passage cultures of human glioblastomas were found to be highly susceptible target cells for H-1 virus mediated cytotoxicity. The formation of fully infectious progeny particles in infected glioma cells offers the chance for the induction of secondary rounds of infection resulting in an advanced cytotoxic effect. These advantageous characteristics of H-1 virus infection of glioma cells, combined with the known low toxicity of H-1 virus in nontransformed cells, make parvovirus H-1 a promising candidate for oncolytic glioma therapy.
First published: 11 December 2003
Gesehen am 19.02.2021